Engaging the fourth industrial revolution Perspectives from theology, philosophy and education - Van den Berg, Jan Albert (Theological Explorations, 2020)
The reality of a radically changing world is beyond dispute. The notion of the Fourth Industrial Revolution is a heuristic key for the world of emerging technologies such as artificial intelligence, nanotechnology, quantum computing, big data, the internet of things, and biotechnology. The discussion of emerging technologies and the Fourth Industrial Revolution highlights urgent questions about issues like intention, function, risk, and responsibility. This publication stimulates further reflection, ongoing conversation, and eventually the production of more textured thinking. The conversation with technology and with thinkers on technology, holds the promise of a certain fecundity, the possibility to see deeper into human evolution, but also, may be, into the future of humankind.